The Effect Of Environmental Performance, Carbon Emissions On Corporate Financial Performance With Code Of Conduct as a Moderating Variable - Hendriyana Hendriyana; Yvonne Agustine (Cita Konsultindo Research Center, 2023)
This study examines the relationship between the issue of environmental performance and carbon emissions on company performance with a code of conduct as a moderating variable. Weather variability in many regions, including Indonesia, has an adverse impact on health in the long term. The strong commitment of the Government of Indonesia has been conveyed in the Paris Agreement and realized with Nationally Determined Contributions (NDC) 29% with its efforts and international support is expected to reduce carbon emissions by 41% in 2030. This commitment is realized by updating Indonesia's NDC by adding the marine and fisheries sector. The effect of environmental performance and Carbon Emissions on the Company's Financial Performance with a moderated Code of Conduct is 49.5%, and 50.5% is influenced by other factors not observed in this study. The Code of Conduct does not have a significant effect directly on the Company's Financial Performance. Develop an operating model of environmental performance in management, and companies can keep the company alive without sacrificing the survival of humanity by reducing these carbon emissions on Earth. This study discusses the difficulties associated with environmental performance, carbon emissions, and codes of conduct in the context of intentional research in management. It offers novel insights into the transformations that firms and management principles and practices should undergo to mitigate irreversible environmental harm.